Intracellular ways of development of Alzheimer's disease against the background of herpes viral infections (literature review) - S.S. Ostrovska; V.F. Shatorna; E.O. Liholetov (Medičnì Perspektivi)
The concept of the viral etiology of Alzheimer's disease (AD) was first proposed in 1982. Its author MJ Ball suggested that the herpes simplex virus (HSV1) may be involved in the pathogenesis of AD, finding that the areas of the brain damaged in acute herpetic encephalitis are the same as those that are affected in AD, and those who survived usually suffer from memory loss and other cognitive impairment typical of AD. Subsequently, in all postmortem brain samples (temporal, frontal, and hippocampal) viral sequences of the viral thymidinekinase gene were found in a high proportion (70-100%) both in AD and in elderly people without it, while in young people and children the virus was found in very low proportions, so it was suggested that HSV1 comes from the peripheral ganglia, where the virus can remain inactive for many years, then enters the brain at an older age due to a decrease in the activity of the immune system. The increased risk of AD is associated with the presence of HSV1 in the brain and the carriage of a specific genetic factor – allele-ε4 of the apolipoprotein E4 gene (APOE-ε4). By themselves, neither HSV1 nor the APOE-ɛ4 allele were found as risk factors for the development of AD but their combination increased the risk of AD development by 12 times and made up 60% in patients with AD. The phenomena involved in the pathophysiology of AD are neurodegenerative changes that occur as a result of fibrillation and deposition of amyloid-β-peptide (Aβ) and neurofibrillary tangles – accumulations of aggregated phosphorylated tau-proteins (P-tau), leading to brain atrophy due to neuronal death. Traditionally, Aβ has been characterized as a catabolic by-product. However, it has recently been shown that Aβ-peptide has antiviral activity and protective effects against HSV infections in the brain. А 16-year study in Thailand with more than 33,000 patients showed that long-term use of antiherpetic drugs reduces the risk of dementia, including AD patients infected with HSV1. Patients with HSV1 infection who received antiherpetic drugs showed a lower risk of all types of dementia compared with the group without these drugs. Their positive effect on stopping the accumulation of amyloid beta and tau protein in the body has been confirmed. In this regard, it is assumed that vaccination against HSV1 may be useful not only for treatment, but also for the prevention of AD.